A Political Stability and the Hidden Crisis of Electoral Legitimacy in Dominant Party Systems - Shogar Bashar Deifa Khateir (UIN Sunan Gunung Djati, 2026)
Tanzania’s democratic transition is often associated with political stability, regular elections, peaceful leadership succession, and respect for presidential term limits. However, this stability has developed alongside persistent concerns over electoral legitimacy, especially because political power has remained largely within the ruling party, CCM. The purpose of this study is to examine how political stability and electoral legitimacy coexist in Tanzania’s dominant-party electoral system. This study uses a qualitative case-study design. It relies on documentary review of academic literature, electoral reports, legal documents, observer reports, and institutional materials related to Tanzania’s multiparty elections. The analysis focuses on political stability, electoral legitimacy, dominant-party continuity, institutional credibility, campaign finance, media access, and Zanzibar’s electoral crisis. The study treats NEC, ZEC, electoral events, and legitimacy claims as the main units of analysis. The principal result shows that Tanzania has achieved political stability through regular elections and peaceful succession, but electoral legitimacy remains contested due to limited inter-party alternation, institutional dependence, unequal competition, and the 2015 Zanzibar annulment. The study concludes that political stability should not be equated with democratic consolidation when electoral institutions and competition remain contested. Its contribution lies in clarifying the distinction between peaceful succession, intra-party turnover, inter-party alternation, and electoral legitimacy in dominant-party electoral systems.